Rural sanitation: Strategies for sanitation in communities in the Municipality of Itaúna - MG (Research, Society and Development, 2024)
The lack of sanitary sewage systems has caused numerous negative consequences to the environment and the integrity of human health in urban areas; and especially in rural areas where this deficit is even greater. In this sense, this research sought to study strategic and technological solutions for sewage services for the rural population of the municipality of Itaúna. This study is guided by the strategies guided by the National Rural Sanitation Program (PNSR), which consider local conditions for choosing solutions, through a technological matrix; and the reference for choosing UNICAMP solutions. With these documents as a theoretical basis, the design study and feasibility analysis for sewage treatment in the rural communities of Carneiros and São José de Pedras in the Municipality of Itaúna were developed. In the design study, a comparative table was drawn up between all possible technological solutions, including efficiency, implementation and maintenance costs, advantages and disadvantages. The feasibility analysis, which considers the importance of continuity of services after implementation, highlighted an individual solution, the evapotranspiration tank for fecal water and the banana tree cycle for gray water. For a collective solution, involving fecal water and ash, the septic tank followed by an anaerobic filter stood out for its efficiency and low maintenance cost. The methodology used in this study, based on local conditions for choosing solutions, appears appropriate to be replicated in other rural locations with a deficit in sanitation.